Applications Of CRISPR Gene Editing Technology in The Genetic Control of Harmful Insects - Awaal Mahmood Lafta (Jurnal MIPA dan Pembelajarannya, 2026)
The Reasons for Rapidly Increasing Use of Insecticides in Society as well as from Environmental Restrictions Placing Limitations on the use of Conventional Methods for Controlling Harmful Insects has Heightened the Need for New Innovative Sustainable Approaches to Manage Pest Insects. To this end, this Study Investigated the Feasibility of the Use of CRISPR/Cas9 Genome Editing Technology to Genetically Control Medically Important Insects and Agricultural Pests (e.g. Anopheles gambiae, Aedes aegypti and Spodoptera frugiperda). Genes Associated with Reproduction, Host-Seeking Behaviour, Viral Susceptibility and Insecticide Resistance were Chosen as Targets for CRISPR-Mediated Disruption of Target Genes. sgRNAs were Designed to Target Conserved Regions of Coding Sequences Followed by the Introduction of CRISPR-Cas9 Ribonucleoproteins into Insect Embryos Via Microinjection Procedures. The Genome Editing Efficiency, Suppression of Target Gene Expression, Phenotypic Changes and Susceptibility of Insects to Insecticides were Evaluated using Molecular and Biological Assays. All of the insect species studied were successfully genome-edited, with editing efficiencies from 41.8% to 67.3%. Quantitative real-time PCR analysis showed that edited insects had substantially lower levels of target gene expression than wild-type controls. The disruption of the doublesex gene in Anopheles gambiae caused significant reductions in fertility and egg hatchability, suggesting that Edited insects had reduced reproductive fitness. In Aedes aegypti, editing of the orco gene resulted in decreased host-seeking behaviours and decreased blood-feeding behaviour. In addition, edited Spodoptera frugiperda larvae had significantly increased susceptibility to Bacillus thuringiensis (Bt) toxins and regular insecticides following CRISPR-mediated disruption of ATP-binding cassette transporter genes and cytochrome P450 monooxygenase genes. Edited larvae also showed significantly reduced feeding behaviour and delayed larval development. Our results indicate that CRISPR-Cas9 is a promising new method to genetically suppress harmful insect populations, and could be used as an environmentally-sustainable alternative to chemical insecticides. We have documented that CRISPR can specifically target genes related to reproduction, vector competence, and the detoxification pathways of insects; thus making it a powerful tool for producing genetically modified organisms (GMOs). However, more research to address ecological safety, off-targets and the long-term environmental safety of these technologies must take place before they are broadly used throughout the environment.